Does food disgust has a relationship with Orthorexia Nervosa? Correlation with gender and body mass index: Food Disgust and the Relationship to Orthorexia Nervosa - Arusoglu, Gülcan (Progress in Nutrition, 2020)
Objective: This study was conducted to determine the association of the predisposition to food disgust and orthorexic tendencies to gender, BMI and some variables. It is the first study to assess food disgust, disgust propensity and sensitivity and its relationship to orthorectic tendencies in Turkish sample. Method: The study was conducted on a total of 300 young individuals, consisting of 199 males and 101 females. The Food Disgust Scale (FDS), Orthorexia Nervosa (ON) (ORTO-11) Scale, Disgust Propensity and Sensitivity Scale- Revised (DPSS-R) and a personal information form were administered. Result: The average age of the individuals was 24.28±6.60 year. The mean BMI of men (23.88 ± 3.31 kg/m2) was significantly higher than women (21.64 ± 3.50 kg/m2) (p <0.001). The mean DPSS-R of women (51.09 ± 12.49) was significantly higher than men (46.67 ± 12.21). The mean DPSS-R in the underweight category (59.92 ± 9.96) was significantly higher in both the normal category (48.10 ± 12.37) and the overweight category (46.33 ± 12.17) (p values ​​0.004 and 0.001, respectively). As a result of simple linear regression analysis performed for DPSS-R, female gender increased DPSS-R by 4.42 units according to male gender (p = 0.004). Correlation coefficients of the FDS and DPSS-R were found to be positive, moderate (r = 0.45, p <0.001). Discussion: It is suggested that the individuals, and may be the patient groups in the future, should be administered the FDS and DPSS-R scale to identify the prevalence in the public and to determine their food disgust sensitivities in further studies. In the future studies of this data specific to our country is intended to be used as a reference.